Environmental justice and environmentalism : the social justice challenge to the environmental movement - Sandler, Ronald D.; Pezzullo, Phaedra C. (Urban and industrial environments., 2007)
Analysis and case studies from interdisciplinary perspectives explore the possibility and desirability of collaboration between the grassroots-oriented environmental justice movement and mainstream environmental organizations.